Numerical Solutions of the Viscous Flow Past a Circular Cylinder with Stream-Wise Velocity Fluctuations - Goddard, V.P.; Szewczyk, A.A. (Engineering Transactions, 1974)
Numerical solutions of the incompressible, two-dimensional, time-dependent Navier-Stokes equations have been obtained for the flow past a circular cylinder with free-stream velocity fluctuations in the flow direction. The fluctuations in the flow are produced by a change in magnitude only and not in direction. The resulting time-dependent equations are solved by the use of an explicit finite-difference scheme possessing conservative and transportive properties for a stream function-vorticity formulation. A variable mesh structure is selected to provide a cell size that is consistent with the structure of the flow, i.e., a fine mesh in regions of large gradients. Results are presented for Reynold’s number 40 and 200, and non-dimensionalized free-stream frequencies of 0.02 to 3.2. The results compare favorably with the analytical work of LIGHTHILL [9] and the experimental works of CHEN and BALLENGEE [2], and TATSUNO [16].